2023
DOI: 10.5946/ce.2022.211
|View full text |Cite
|
Sign up to set email alerts
|

Covered self-expandable metallic stents versus plastic stents for endoscopic ultrasound-guided hepaticogastrostomy in patients with malignant biliary obstruction

Abstract: Background/Aims: Covered self-expandable metallic stents (cSEMS) have become popular for endoscopic ultrasound-guided hepaticogastrostomy with transmural stenting (EUS-HGS). We compared the time to recurrent biliary obstruction (TRBO), complications, and reintervention rates between EUS-HGS using plastic stent (PS) and cSEMS in patients with unresectable malignancies at multicenter institutions in Japan. Methods: Patients with unresectable malignant biliary obstruction who underwent EUS-HGS between April 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Furthermore, the median survival time was 60 days shorter in the EUS-HGSB group than in the ETBD-MS group. This could have contributed to the finding of longer stent patency with EUS-HGSB than with ETBD-MS. Because duration of patency for EUS-HGS and ETBD-MS with SEMS in distal obstruction has been reported to be approximately 1 year 26 27 and 6 months 5 6 , respectively, the observation period in this study appears inadequate. In addition, the stents placed via the EUS-HGS route were not standardized in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the median survival time was 60 days shorter in the EUS-HGSB group than in the ETBD-MS group. This could have contributed to the finding of longer stent patency with EUS-HGSB than with ETBD-MS. Because duration of patency for EUS-HGS and ETBD-MS with SEMS in distal obstruction has been reported to be approximately 1 year 26 27 and 6 months 5 6 , respectively, the observation period in this study appears inadequate. In addition, the stents placed via the EUS-HGS route were not standardized in this study.…”
Section: Discussionmentioning
confidence: 89%
“…[48] Unfortunately, this stent is only available in Japan, and therefore a 7-Fr doublepigtail plastic stent may be an alternative option due to its widespread availability and affordability. [49] Shibuki et al [50] retrospectively reviewed patients who underwent EUS-HGS.…”
Section: Manuscriptmentioning
confidence: 99%
“…PDT is associated with an incidence of phototoxic reaction in 11.11%. [57] Kang et al [50] reported a RCT in 2022 comparing RFA plus bilateral PS and bilateral PS alone in 30 patients. The study showed that RFA significantly reduced premature PS occlusion within 3 months when compared with bilateral PS alone (30.8% vs 76.9% respectively, p = 0.018), while adverse events were not different between the 2 groups.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Most adverse events were mild in severity with peritonitis developing in 4.4% of cases. Another multicenter retrospective study ( n = 152, 40.8% PDAC) from Japan compared the use of SEMS with plastic stents for EUS-HG, finding that SEMS had a longer stent patency duration (646 days vs. 202 days) with no difference in clinical success rates [ 22 ]. A multicenter prospective study ( n = 49, 22.4% PDAC) found that EUS-HG combined with antegrade biliary stenting carried a technical success rate of 85.7% [ 23 ].…”
Section: Eus-based Treatment Modalitiesmentioning
confidence: 99%